A seemingly tricky problem but NICEEEE!

Algebra Level pending

What is the sum of all possible solutions for x of the equation x ( x - k ) = k + 1?

1 k+1 k 0

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Agnibha Sen
May 2, 2014

Any quadratic equations in x with two roots a and b can be expressed as, (x - a)(x - b) = 0. Which on expansion takes the form, x² - (a + b)x - ab = 0

Hence, the sum of the roots = -(coefficient of x in the expanded form)

Now, x(x - k) = k + 1 => x² - kx - (k + 1) = 0

Hence, sum of the roots = -(-k) = k

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...